2012
DOI: 10.1530/eje-11-0646
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Micro-RNAs: targets for enhancing osteoblast differentiation and bone formation

Abstract: Osteoblast differentiation and bone formation (osteogenesis) are regulated by transcriptional and posttranscriptional mechanisms. Recently, a novel class of regulatory factors termed micro-RNAs (miRNAs) has been identified as playing an important role in the regulation of many aspects of osteoblast biology including proliferation, differentiation, metabolism and apoptosis. Also, preliminary data from animal disease models suggest that targeting miRNAs in bone can be a novel approach to increase bone mass. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 141 publications
3
83
0
1
Order By: Relevance
“…Our study showed that miR-93 was involved in osteoblast mineralization and exerted its roles through interaction with the bone-specific factor Sp7. miRNAs made contributions in osteoblast differentiation, (20) but the mechanisms of their actions in osteoblast mineralization have not been clearly shown. In the present study, microarray analysis revealed that miR-93 exhibited maximal change during osteoblast mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that miR-93 was involved in osteoblast mineralization and exerted its roles through interaction with the bone-specific factor Sp7. miRNAs made contributions in osteoblast differentiation, (20) but the mechanisms of their actions in osteoblast mineralization have not been clearly shown. In the present study, microarray analysis revealed that miR-93 exhibited maximal change during osteoblast mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…Computational prediction of targets relies on the pairing of the seed sequence of the miRNA to a complementary 3 0 UTR following strict base-pairing rules. 42 In the current study, several important binding sites of miR-152 to the 3 0 UTR of DKK1 mRNA were identified. DKK1 has been reported to be overexpressed in MM and in other cancers such as hepatoblastoma, Wilm's tumors and breast cancer.…”
Section: Discussionmentioning
confidence: 67%
“…Con, control; Dex, dexamethasone; NC, negative control; miR, microRNA. Ma et al 2012, Taipaleenmaki et al 2012, Wei et al 2012, Xu et al 2012a,b, Chiyomaru et al 2013. Furthermore, these miRNAs could mediate WNT signaling (Chiyomaru et al 2013, Nagano et al 2013, Guo et al 2014, Rathod et al 2014, Hashemi et al 2015, a crucial factor in decreased bone formation in response to GCs.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs may also promote the translation of selected mRNAs in a cell-cycle-phase-dependent way (Zeng 2006). Results of recent studies have indicated that some miRNAs, such as miR-27a, miR-29a, miR-34a, miR-125b, miR-133, miR-138, miR-199a, miR-206, miR-338, miR-335, and miR-378, play a crucial role in bone formation (Taipaleenmaki et al 2012). Furthermore, results of previous studies have indicated that many of these miRNAs, including miR-27a, miR-29a, miR-34a, miR-125b, miR-199a, and miR-574, could mediate cell proliferation , Ma et al 2012, Wei et al 2012, Xu et al 2012a,b, Chiyomaru et al 2013.…”
Section: Introductionmentioning
confidence: 99%